Traditional birth attendants (TBAs) as potential agents in promoting male involvement in maternity preparedness: insights from a rural community in Uganda. Issue 1 (December 2016) - Turinawe, Emmanueil; Rwemisisi, Jude; Musinguzi, Laban; de Groot, Marije; Muhangi, Denis; de Vries, Daniel; Mafigiri, David; Katamba, Achilles; Parker, Nadine; Pool, Robert
Abstract Background Since the 1994 International Conference on Population and Development, male involvement in reproductive health issues has been advocated as a means to improve maternal and child health outcomes, but to date, health providers have failed to achieve successful male involvement in pregnancy care especially in rural and remote areas where majority of the underserved populations live. In an effort to enhance community participation in maternity care, TBAs were trained and equipped to ensure better care and quick referral. In 1997, after the advent of the World Health Organization's Safe Motherhood initiative, the enthusiasm turned away from traditional birth attendants (TBAs). However, in many developing countries, and especially in rural areas, TBAs continue to play a significant role. This study explored the interaction between men and TBAs in shaping maternal healthcare in a rural Ugandan context. Methods This study employed ethnographic methods including participant observation, which took place in the process of everyday life activities of the respondents within the community; 12 focus group discussions, and 12 in-depth interviews with community members and key informants. Participants in this study were purposively selected to include TBAs, men, opinion leaders like village chairmen, and other key informants who had knowledge about the configuration of maternity services in the community. Data analysis was done inductively through an iterative process in which transcribed data was read to identify themes and codes were assigned to those themes. Results Contrary to the thinking that TBA services are utilized by women only, we found that men actively seek the services of TBAs and utilize them for their wives' healthcare within the community. TBAs in turn sensitize men using both cultural and biomedical health knowledge, and become allies with women in influencing men to provide resources needed for maternity care. Conclusion In this study area, men trust and have confidence in TBAs; closer collaboration with TBAs may provide a suitable platform through which communities can be sensitized and men actively brought on board in promoting maternal health services for women in rural communities.